INOVASI BANK SAMPAH DESA SAMBAK: PEMBERDAYAAN MASYARAKAT MELALUI EKONOMI SIRKULAR DAN PRODUKSI PAVING BLOCK DENGAN TEKNOLOGI INCINERATOR - Maulia Siti Mukharohmah; Jihad Lukis Panjawa; Arif Rahman Saleh; Dinar Melani Hutajulu; Yesinta Nanda Kurnia; Katarina Putri Maharani (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2026)
Sambak Village, recognized as a Proklim Lestari awardee, continues to face challenges in managing non-recyclable plastic waste with low market value, which often ends up in open burning practices that harm the environment. This community service program introduces an innovative solution through the development of the Sambak Village Waste Bank by integrating circular economy principles with the application of low-emission incinerator technology for paving block production. The activities were implemented through capacity building, tutorials, and mentoring sessions involving local residents, waste bank managers, and micro-entrepreneurs. Plastic waste was processed using an incinerator fueled by waste cooking oil and used lubricants, producing semi-processed by-products that were then utilized in paving block manufacturing. Program implementation encouraged community participation in waste segregation, technical training, and collaborative production, while monitoring and evaluation highlighted significant improvements in institutional governance and reduced environmental impacts compared to traditional burning. Beyond technical outcomes, the initiative enhanced community awareness, fostered behavioral change toward sustainable waste management, and opened economic opportunities through the commercialization of paving blocks. This program illustrates an effective model of community empowerment that transforms plastic waste into value-added products, reinforcing Sambak Village as a pioneer of environmentally friendly and climate-resilient practices.